Study on Extractable Major Ions in Bottom Ash from Municipal Solid Waste Incinerators - Minh Phuong, Nguyen; Hoang Hiep, Tran; Thi Nham, Nguyen; Manh Ha, Nguyen; Minh Viet, Nguyen; Thi Hoang Lien, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Along with population growth and increasing social demands, the volume of municipal solid waste (MSW) has been rising significantly. At present, municipal solid waste incinerators are being widely used in many localities. This method considerably reduces both the volume and mass of waste; however, a large amount of bottom ash generates. Bottom ash is a solid residue that primarily accumulates non-volatile components such as metal oxides (silicon, iron, aluminum, etc.) or carbonate, sulfate, and chloride salts of sodium, potassium, calcium, and magnesium. In this study, the concentrations of extractable major ions (Na⁺, K⁺, Ca²⁺, Mg²⁺) in bottom ash from municipal solid waste incineration were investigated under different conditions (extraction time, solid–liquid ratio, and type of extractant). The results show that the shaking time of four hours and a solid-to-liquid ratio of 1:25 are suitable for extracting the major ions Na⁺, K⁺, Ca²⁺, and Mg²⁺ from municipal solid waste incineration ash samples. In addition, citric acid is an effective and selective extracting agent for Ca²⁺ ion. The obtained results provide a scientific basis for further research on the recovery of valuable components from bottom ash, thereby contributing to its effective reuse.